Some cross-validity studies involving the college test - Iledan, Basilio R. (Philippine Journal of Psychology, 1974)
Predictor set suppressor variables from the Gumban and Iledan (1971)study were analyzed for validity and the predictive efficiency of the College Entrance Test were interpreted in more simple statistical terms.Regression equations were developed and cross-validity performed on validation samples from different schools for the specific purpose of finding some indications of usefulness of the equations for prediction outside of the school population from which the derivation samples were obtained.